2020
DOI: 10.1002/ajmg.a.61531
|View full text |Cite
|
Sign up to set email alerts
|

Loss‐of‐function of Endothelin receptor type A results in Oro‐Oto‐Cardiac syndrome

Abstract: Craniofacial morphogenesis is regulated in part by signaling from the Endothelin receptor type A (EDNRA). Pathogenic variants in EDNRA signaling pathway components EDNRA, GNAI3, PCLB4, and EDN1 cause Mandibulofacial Dysostosis with Alopecia (MFDA), Auriculocondylar syndrome (ARCND) 1, 2, and 3, respectively. However, cardiovascular development is normal in MFDA and ARCND individuals, unlike Ednra knockout mice.One explanation may be that partial EDNRA signaling remains in MFDA and ARCND, as mice with reduced, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The GO and pathway enrichment analysis of DEG are closely related to obesity associated type 2 diabetes mellitus. Genes such as KCNE5 [ 45 ], SHANK3 [ 46 ], CASQ2 [ 47 ], EDNRA (endothelin receptor type A) [ 48 ], EPHB4 [ 49 ], ALPK3 [ 50 ], WNT11 [ 51 ], IRAK2 [ 52 ], FBN1 [ 53 ], SFRP2 [ 54 ], CLCA2 [ 55 ], NEXN (nexilin F-actin binding protein) [ 56 ], PALLD (palladin, cytoskeletal associated protein) [ 57 ], DAB2 [ 58 ], NRP2 [ 59 ], THBS2 [ 60 ], CSF1R [ 61 ], KCNA2 [ 62 ], CACNA1C [ 63 ], F2R [ 64 ], UCHL1 [ 65 ], CCL18 [ 66 ], ITGB1BP2 [ 67 ] and FMOD (fibromodulin) [ 68 ] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [ 69 ], Liu et al [ 70 ], Eltokhi et al [ 71 ], Cai et al [ 72 ], Pfeiffer et al [ 73 ], Lin et al [ 74 ], Royer-Zemmour et al [ 75 ], Pastor et al [ 76 ], Goodspeed et al [ 77 ], Zhang et al [ 78 ], Rogers et al [ 79 ], Su et al [ 80 ] and Foale et al [ 81 ] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were the genes expressed in progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis of DEG are closely related to obesity associated type 2 diabetes mellitus. Genes such as KCNE5 [ 45 ], SHANK3 [ 46 ], CASQ2 [ 47 ], EDNRA (endothelin receptor type A) [ 48 ], EPHB4 [ 49 ], ALPK3 [ 50 ], WNT11 [ 51 ], IRAK2 [ 52 ], FBN1 [ 53 ], SFRP2 [ 54 ], CLCA2 [ 55 ], NEXN (nexilin F-actin binding protein) [ 56 ], PALLD (palladin, cytoskeletal associated protein) [ 57 ], DAB2 [ 58 ], NRP2 [ 59 ], THBS2 [ 60 ], CSF1R [ 61 ], KCNA2 [ 62 ], CACNA1C [ 63 ], F2R [ 64 ], UCHL1 [ 65 ], CCL18 [ 66 ], ITGB1BP2 [ 67 ] and FMOD (fibromodulin) [ 68 ] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [ 69 ], Liu et al [ 70 ], Eltokhi et al [ 71 ], Cai et al [ 72 ], Pfeiffer et al [ 73 ], Lin et al [ 74 ], Royer-Zemmour et al [ 75 ], Pastor et al [ 76 ], Goodspeed et al [ 77 ], Zhang et al [ 78 ], Rogers et al [ 79 ], Su et al [ 80 ] and Foale et al [ 81 ] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were the genes expressed in progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis of DEG are closely related to obesity associated type 2 diabetes mellitus genes and advancement. KCNE5 [45], SHANK3 [46], CASQ2 [47], EDNRA (endothelin receptor type A) [48], EPHB4 [49], ALPK3 [50], WNT11 [51], IRAK2 [52], FBN1 [53], SFRP2 [54], CLCA2 [55], NEXN (nexilin F-actin binding protein) [56], PALLD (palladin, cytoskeletal associated protein) [57], DAB2 [58], NRP2 [59], THBS2 [60], CSF1R [61], KCNA2 [62], CACNA1C [63], F2R [64], UCHL1 [65], CCL18 [66], ITGB1BP2 [67] and FMOD ( bromodulin) [68] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [69], Liu et al [70], Eltokhi et al [71], Cai et al [72], Pfeiffer et al [73], Lin et al [74], Royer-Zemmour et al [75], Pastor et al [76], Goodspeed et al [77], Zhang et al [78], Rogers et al [79], Su et al [80] and Foale et al [81] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were linked with progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…variants in EDNRA (MIM 131243), though the variants affect EDNRA function differently. The OOCSassociated disease variant, EDNRA p.Gln381Pro, disrupts receptor-Gq/11 association and abrogates signaling, leading to cardiac and craniofacial defects resembling the mouse Ednra knockout phenotype, including neonatal lethality (Pritchard et al, 2020). The MFDA-associated disease variants, EDNRA p.Tyr129Phe (c.386A>T) and EDNRA p.Glu303Lys (c.907G>A), likely reduce receptor-EDN1 binding affinity and increase receptor-EDN3 binding affinity, leading to ectopic EDNRA signaling in the maxillary prominence (Gordon et al, 2015).…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 99%
“…To verify the specificity of the BRET signal using this approach, cells were co-transfected with rLuc8-C1A and Lyn-Venus along with EDNRA or a loss-of-function EDNRA variant [EDNRA p.Gln381Pro (c.1142A>C;(Pritchard et al, 2020)]. Subsequent EDN1 treatment produced a ∆BRET response from cells expressing EDNRA but not from cells expressing EDNRA p.Gln381Pro (Fig.…”
Section: Bret Analysis Of Plcb4 Variants Supports a Dominant Negative...mentioning
confidence: 99%
See 1 more Smart Citation